Envelope frequency following responses are stronger for high-pass than low-pass filtered vowels. (3rd June 2019) - Vanheusden, Frederique J.; Chesnaye, Michael A.; Simpson, David M.; Bell, Steven L.
Abstract: Background: To assess hearing in response to speech, the envelope frequency following response (FFR) can be observed at the fundamental frequency of a vowel stimulus and its harmonics. FFRs are complex non-linear phenomena, which require better understanding for allowing robust inferences on the assessment of hearing and hearing aid fitting. Objectives: To evaluate the effect of stimulus bandwidth on FFR detection rates using filtered vowel stimuli with equal sound levels. Design: FFRs were collected whilst presenting repeated vowels (in consonant-vowel-consonant format) filtered into different bandwidths. Eighty stimuli per word were presented at 70 dB SPL LAeq through insert earphones with an inter-stimulus interval of 1 s. Responses were detected using frequency-domain Hotelling's T2 (HT2) tests for individual multiples of the fundamental frequency (F0) and for combinations of F0 multiples. Study sample: A total of 11 native English-speaking subjects with normal hearing thresholds. Results: Average detection rates are highest (69%) with stimuli high-pass filtered >1000 Hz, and significantly lower for low-pass filtered stimuli (40%). Conclusions: High-pass filtered vowels therefore appear to elicit stronger FFRs than low-pass filtered vowels at the same dB SPL LAeq. For testing hearing using band-limited speech, filtering effects (due to hearing loss, hearing aid setting or stimulus choice) on responses must be considered.